Comparing four different methods for the management of ectopic pregnancy: A cross-sectional study - Zahra Shiravani; Sana Atbaei; Bahia Namavar Jahromi; Mojgan Hajisafari Tafti; Shaghayegh Moradi Alamdarloo; Tahereh Poordast; Adel Noori; Sedighe Forouhari; Soudabeh Sabetian (Shahid Sadoughi University of Medical Sciences, 2022)
Abstract Background: Ectopic pregnancy (EP) is one of the major causes of maternal mortality during the first trimester of pregnancy. Objective: Four treatment methods for EP including single-dose methotrexate (SD-MTX), double-dose methotrexate, expectant and surgical management were considered. Materials and Methods: In this cross-sectional study, the clinical characteristics of 365 women aged 15-44 yr who had been diagnosed with EP were reviewed from March 2017 to March 2019 in hospitals affiliated to Shiraz University of Medical Sciences, Shiraz, Iran. Receiver operating characteristics curves were plotted to determine the cut-off points for size of ectopic mass and beta-human chorionic gonadotropin (β-hCG) that suitably discriminated between double-dose methotrexate and surgery management. Results: The most common site of EP was adnexa. According to the receiver operating characteristics analysis, surgery was the best plan for the women with an ectopic mass > 34.50 mm in diameter or with an initial β-hCG level > 6419 mIU/ml. The β-hCG levels in the women successfully treated with SD-MTX were significantly lower than in those with failed treatment (p = 0.02). The SD-MTX group had a higher success rate and significantly shorter duration of hospitalization, and so this was a more effective medical treatment in comparison with the double-dose protocol. Conclusion: Surgery is proposed as the best option for the cases with large ectopic mass or high β-hCG level. SD-MTX had a higher success rate and shorter hospital stay than the double-dose protocol, and so was found to be an efficient and safe alternative. Further randomized clinical trials with larger sample sizes are recommended to validate the current results.